Prospective randomized trial of 5 days azacitidine versus supportive care in patients with lower-risk myelodysplastic syndromes without 5q deletion and transfusion-dependent anemia. Issue 5 (4th May 2018) - Sanchez-Garcia, Joaquin; Falantes, Jose; Medina Perez, Angeles; Hernandez-Mohedo, Francisca; Hermosin, Lourdes; Torres-Sabariego, Angeles; Bailen, Alicia; Hernandez-Sanchez, Jesus M.; Solé Rodriguez, María; Casaño, Francisco Javier; Calderon, Cristina; Labrador, Maria; et al.
Abstract: In this prospective trial, the efficacy of azacitidine in lower-risk myelodysplastic syndromes (LR-SMD) lacking del(5q) was compared to best supportive care (BSC) at 1:1. The primary endpoint was the achievement of erythroid hematologic improvement (HI-E) after nine cycles. Thirty-six patients received at least ≥1 cycle. HI-E was confirmed 44.4% randomized to Aza and in 5.5% of patients receiving BSC ( p < .01). After entry in Aza extension period, transfusion independence was achieved in all Aza responders with a median duration of 50 weeks (range: 17–231). No significant differences were observed in secondary endpoints. Importantly, variant allele frequency (VAF) of some mutated genes ( RET, SF3B1, ASXL1) decreased after 9 months of treatment in Aza-responder patients. In conclusion, LR-MDS patients lacking del5q and resistant to ESAs, who receive 5 days Aza, achieve TI in a substantial proportion of cases and results in modifications in mutational landscape.